PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA BENGKULU DALAM PERSPEKTIF NILAI EKONOMI ISLAM - Juliah Alisah; Yosy Arisandy; Rahmat Putra Ahmad Hasibuan (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the effect of tax knowledge, taxpayer awareness, and service quality on taxpayer compliance in Bengkulu City from the perspective of Islamic economic values. This study employed a quantitative approach using primary data collected through questionnaires distributed to taxpayers in Bengkulu City. The sampling technique used was purposive sampling, resulting in 170 respondents as the research sample. The research data were analyzed using multiple linear regression with the assistance of SPSS version 26 software to examine the effect of each variable on taxpayer compliance. The findings of this study indicate that tax knowledge, taxpayer awareness, and service quality have a positive and significant effect on taxpayer compliance. In addition, taxpayer awareness is the most dominant variable influencing taxpayer compliance. The coefficient of determination (R²) of 0.746 indicates that tax knowledge, taxpayer awareness, and service quality explain 74.6% of taxpayer compliance, while the remaining 25.4% is influenced by other variables outside the scope of this study. From the perspective of Islamic economic values, taxpayer compliance reflects the implementation of the principles of trustworthiness (amanah), justice ('adl), and public welfare (maslahah) as a form of social responsibility in supporting development and community welfare.